Magnetic shape memory alloy with low hysteresis and giant magnetoheat and preparation method thereof

By introducing Ti elements into NiCoMnIn alloy and using arc smelting and high temperature annealing quenching treatment, the alloy has solved the problem of large phase transition span and high thermal hysteresis during the martensite phase transition process, and the effects of low hysteresis giant magnetothermal and high magnetic entropy change are achieved.

CN119553162APending Publication Date: 2025-03-04HEBEI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411663388.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04

Smart Images

  • Figure CN119553162A_ABST
    Figure CN119553162A_ABST
Patent Text Reader

Abstract

The invention relates to a magnetic shape memory alloy with low hysteresis and giant magnetoheat. The chemical formula of the magnetic shape memory alloy is Ni < 40 > Co < 10 > Mn < 36 > Ti < 11 > In < 3 >. The invention also relates to a preparation method of the magnetic shape memory alloy with low hysteresis and giant magnetoheat, which comprises the following steps: putting the weighed materials in a smelting furnace, carrying out electric arc smelting to obtain a spindle, and carrying out high-temperature treatment on the spindle to obtain Ni40Co10Mn36Ti11In3. The phase change span of Ni40Co10Mn36Ti11In3 is small, the thermal hysteresis is small, the magnetic entropy change is large, and 80% of martensite phase change can occur under a 5T magnetic field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy synthesis, and in particular to a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties and a preparation method thereof. Background Art

[0002] NiCoMnIn magnetic memory alloy is a new functional material with thermoelastic martensitic phase transformation, which can be induced by temperature, stress and magnetic field. It has good shape memory effect, magnetocaloric effect, giant magnetoresistance effect and elastocaloric effect, and can be used as a sensor, driver and room temperature solid-state refrigerant. The martensitic phase transformation of NiCoMnIn polycrystalline alloy has a large phase transition span, high thermal hysteresis and a high critical magnetic field for inducing phase transformation.

[0003] Chinese patent CN108950275A discloses a method for synthesizing NiCoMnIn magnetic memory alloy by combustion reaction at high temperature. NiCoMnIn magnetic memory alloy is prepared by the following steps: taking 45-48 parts of Ni powder, 34 parts of Mn powder, 16 parts of In powder and 5-2 parts of Co powder according to atomic percentage, stirring the metal powders by a stirrer to mix them evenly, then pouring them into a pressure forming mold, pressing the powders into a cylindrical sample with a jack, putting them into a box-type resistance furnace for sintering, and then cooling them to room temperature with the furnace and taking them out to obtain NiCoMnIn magnetic memory alloy. The magnetic shape memory alloy NiCoMnIn prepared by the present invention has the advantages of good toughness, high strength, fine structure, etc.

[0004] Chinese patent CN108677078A discloses a Mn-rich Mn-Ni-In-Co-Cu magnetic refrigeration material and a preparation method thereof. The material itself can obtain excellent adiabatic temperature change near room temperature and is an ideal near-room temperature magnetic refrigeration medium. The chemical formula of the Mn-rich Mn-Ni-In-Co-Cu magnetic refrigeration alloy material is MnxNi37In9Co4Cuy, and the sum of the molar numbers of elements in the alloy is 100, where 46≤x≤49, 1≤y≤4. The present invention prepares a polycrystalline ingot by raw material proportioning and repeated smelting of a vacuum arc, annealing under the protection of a high-purity inert gas, and then rapidly water cooling, thereby preparing a Mn-rich Mn-Ni-In-Co-Cu magnetic refrigeration alloy block blank. The alloy block of the present invention has a magnetic entropy change range of 4.4 to 15.8JKg-1K-1 under a 3T magnetic field.

[0005] At present, NiCoMnIn alloys generally have a large phase transition span, large thermal hysteresis, relatively low magnetic entropy change, and a high critical magnetic field to induce phase transition. Summary of the invention

[0006] The object of the present invention is to provide a magnetic shape memory alloy with low hysteresis giant magnetocaloric and a preparation method thereof, by selecting suitable metals and proportions, melting the alloy into an ingot by arc melting, then placing it in a high temperature furnace for annealing, and then quenching it at high temperature, which can effectively reduce

[0007] Ni 40 Co 10 Mn 36 Ti 11 In3 thermal hysteresis and phase transition span.

[0008] The technical solution of the present invention:

[0009] A magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties, wherein the chemical formula of the magnetic shape memory alloy is: Ni 40 Co 10 Mn 36 Ti 11 In3.

[0010] A method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties, wherein the weighed material is placed in a melting furnace, arc melting is used to obtain an ingot, and the ingot is subjected to high temperature treatment to obtain Ni 40 Co 10 Mn 36 Ti 11 In3.

[0011] Preferably, the arc melting step is: draw a vacuum to a vacuum degree of 2.3×10 -4 Pa, introduce argon gas to make the internal pressure of the furnace chamber reach 0.1Mpa, generate an arc, and repeat the melting three times. The arc head swings repeatedly 2-3cm above the weighed material for melting.

[0012] Preferably, the first smelting current is increased from 50A to 90A, and the smelting is carried out for 30 to 50s; the second smelting current is increased from 45A to 90A, and the smelting is carried out for 30 to 40s; and the third smelting current is increased from 45A to 85A, and the smelting is carried out for 30 to 40s.

[0013] Preferably, the ingot is subjected to high temperature treatment steps as follows: the ingot obtained by arc melting is placed in a sealed quartz tube, subjected to high temperature homogenization treatment at 950°C for 96 hours, and then quenched to achieve a highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 Ti 11 In3 magnetic shape memory alloy polycrystalline ingot.

[0014] Preferably, the quenching process is to heat the sample to 950°C, immerse it in a 0°C ice-water mixture, and perform a cooling treatment for 15-25 minutes.

[0015] Preferably, the molar ratio of nickel block: cobalt block: manganese block: titanium block: indium block in the weighed material is 40:10:36-36.72:11:3.

[0016] Preferably, the purity of nickel Ni, cobalt Co, manganese Mn, titanium Ti and indium In is not less than 99.9%.

[0017] Beneficial effects of the present invention:

[0018] The present invention Ni 40 Co 10 Mn 36 Ti 11 In3 has a small phase transition span, small thermal hysteresis, large magnetic entropy change, and 80% of the martensitic phase transition can occur under a 5T magnetic field. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 MT curves of Example 1 of the present invention measured under 100Oe and 50kOe magnetic fields;

[0020] Figure 2 MH curves measured at different temperatures in Example 1 of the present invention;

[0021] Figure 3 is a phase change volume fraction diagram of Example 1 of the present invention at different temperatures;

[0022] Figure 4 Calculate ΔS by Maxwell's formula for Example 1 of the present invention M picture;

[0023] Figure 5 This is the ICP-OES composition measurement of Example 1 of the present invention. DETAILED DESCRIPTION

[0024] Example 1 Preparation of Ni 40 Co 10 Mn 36 Ti 11 In3 polycrystalline

[0025] Weighing ratio: According to the chemical formula Ni 40 Co 10 Mn 36 Ti 11 The atomic percentage of In3 is weighed: nickel with a purity of 99.9%, cobalt with a purity of 99.9%, manganese with a purity of 99.9%, titanium with a purity of 99.9%, and indium with a purity of 99.9%; the mass ratio of the components in the weighed materials is nickel block: cobalt block: manganese block: titanium block: indium block, and the mass ratio is 40:10:36:11:3.

[0026] Melting to prepare polycrystalline ingots: Place the weighed materials in a melting furnace and draw a vacuum to a degree of 2.3×10 - 4 Pa, argon gas is introduced to make the internal pressure of the furnace chamber reach 0.1Mpa, an arc is generated, and the melting is repeated three times. The arc head repeatedly swings and melts 2-3cm above the weighed material. The first melting current is increased from 50A to 90A, and the melting is continued for 30s; the second melting current is increased from 45A to 90A, and the melting is continued for 30s; the third melting current is increased from 45A to 85A, and the melting is continued for 40s.

[0027] High temperature treatment sample: The ingot obtained by arc melting was placed in a sealed quartz tube and subjected to high temperature homogenization treatment at 950°C for 96 hours. Then the sample was heated to 950°C, immersed in a 0°C ice-water mixture, and cooled for 20 minutes to achieve a highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 Ti 11 In3 magnetic shape memory alloy polycrystalline ingot (see Figure 5 ).

[0028] Figure 1 The MT curves of Example 1 of the present invention measured under 100Oe and 50kOe magnetic fields are shown in FIG. 40 Co 10 Mn 36 Ti 11 The phase change span of In3 magnetic shape memory alloy polycrystalline ingot is small and the thermal hysteresis is small.

[0029] Figure 2 MH curves measured at different temperatures in Example 1 of the present invention; indicating that the magnetic field can induce the Ni prepared in Example 1 of the present invention 40 Co 10 Mn 36 Ti 11 In3 magnetic shape memory alloy polycrystalline ingot undergoes martensitic phase transformation.

[0030] Figure 3 It is a phase transformation volume fraction diagram of Example 1 of the present invention at different temperatures, indicating that 80% of the martensitic phase transformation can occur under a 5T magnetic field.

[0031] Figure 4 Calculate ΔS by Maxwell's formula for Example 1 of the present invention M Figure: Ni prepared in Example 1 of the present invention 40 Co 10 Mn 36 Ti 11In3 magnetic shape memory alloy polycrystalline ingot can reach 39J / kgK at 327K, which is a large magnetic entropy change value.

[0032] Example 2 Preparation of Ni 40 Co 10 Mn 36 Ti 10 In4 Polycrystalline

[0033] Weighing ratio: According to the chemical formula Ni 40 Co 10 Mn 36 Ti 10 The atomic percentage of In4 is weighed: nickel with a purity of 99.9%, cobalt with a purity of 99.9%, manganese with a purity of 99.9%, titanium with a purity of 99.9%, and indium with a purity of 99.9%; the mass ratio of the components in the weighed materials is nickel block: cobalt block: manganese block: titanium block: indium block, and the mass ratio is 40:10:36.72:11:3.

[0034] Melting to prepare polycrystalline ingots: Place the weighed materials in a melting furnace and draw a vacuum to a degree of 2.3×10 - 4 Pa, argon gas is introduced to make the internal pressure of the furnace chamber reach 0.1Mpa, an arc is generated, and the melting is repeated three times. The arc head is repeatedly swung 2-3cm above the weighed material to melt. The first melting current is increased from 50A to 90A, and the melting is continued for 40s; the second melting current is increased from 45A to 90A, and the melting is continued for 40s; the third melting current is increased from 45A to 85A, and the melting is continued for 30s.

[0035] High temperature treatment sample: The ingot obtained by arc melting was placed in a sealed quartz tube and subjected to high temperature homogenization treatment at 950°C for 96 hours. Then the sample was heated to 950°C, immersed in a 0°C ice-water mixture, and cooled for 15 minutes to achieve a highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 Ti 10 In4 magnetic shape memory alloy polycrystalline ingot.

[0036] Example 3 Preparation of Ni 40 Co 10 Mn 36 Ti 11.5 In 2.5 polycrystalline

[0037] Weighing ratio: According to the chemical formula Ni 40 Co 10 Mn 36 Ti 11The atomic percentage of In3 is weighed: nickel with a purity of 99.9%, cobalt with a purity of 99.9%, manganese with a purity of 99.9%, titanium with a purity of 99.9%, and indium with a purity of 99.9%; the mass ratio of the components in the weighed materials is nickel block: cobalt block: manganese block: titanium block: indium block, and the mass ratio is 40:10:36.50:11:3.

[0038] Melting and preparation of polycrystalline ingots: The weighed materials are placed in a melting furnace and vacuum is drawn to a vacuum degree of 2.3×10 - 4 Pa, argon gas is introduced to make the internal pressure of the furnace chamber reach 0.1Mpa, an arc is generated, and the melting is repeated three times. The arc head is repeatedly swung and melted 2-3cm above the weighed material. The first melting current is increased from 50A to 90A, and the melting is continued for 50s; the second melting current is increased from 45A to 90A, and the melting is continued for 35s; the third melting current is increased from 45A to 85A, and the melting is continued for 35s.

[0039] High temperature treatment sample: The ingot obtained by arc melting was placed in a sealed quartz tube and subjected to high temperature homogenization treatment at 950°C for 96 hours. The sample was then heated to 950°C, immersed in a 0°C ice-water mixture, and cooled for 25 minutes to achieve a highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 Ti 11.5 In 2.5 Magnetic shape memory alloy polycrystalline ingot.

[0040] Comparative Example 1

[0041] Weighing ratio: According to the chemical formula Ni 40 Co 10 Mn 36 Ti 10 The atomic percentage of In4 is 99.9% nickel, 99.9% cobalt, 99.9% manganese, 99.9% titanium and 99.9% indium. The mass ratio of the components in the weighed materials is 40:10:36:11:3 for nickel block:cobalt block:manganese block:titanium block:indium block.

[0042] Melting and preparation of polycrystalline ingots: The weighed materials are placed in a melting furnace and vacuum is drawn to a vacuum degree of 2.3×10 - 4Pa, argon gas is introduced to make the internal pressure of the furnace chamber reach 0.1Mpa, an arc is generated, and the melting is repeated three times. The arc head is repeatedly swung 2-3cm above the weighed material to melt. The first melting current is increased from 50A to 90A, and the melting is continued for 30s; the second melting current is increased from 45A to 90A, and the melting is continued for 30s; the third melting current is increased from 45A to 85A, and the melting is continued for 40s. Ni is obtained 40 Co 10 Mn 36 Ti 11 In3 magnetic shape memory alloy polycrystalline ingot.

[0043] Ni without high temperature treatment 40 Co 10 Mn 36 Ti 11 The magnetic strength of In3 magnetic shape memory alloy polycrystalline ingot is far inferior to that of the sample treated at high temperature, and it has large thermal hysteresis and small magnetization intensity.

[0044] Comparative Example 2

[0045] Weighing ratio: According to the chemical formula Ni 40 Co 10 Mn 36 Ti 10 The atomic percentage of In4 is 99.9% nickel, 99.9% cobalt, 99.9% manganese, 99.9% titanium and 99.9% indium. The mass ratio of the components in the weighed materials is 40:10:36:10:4: nickel block: cobalt block: manganese block: titanium block: indium block.

[0046] Melting and preparation of polycrystalline ingots: The weighed materials are placed in a melting furnace and vacuum is drawn to a vacuum degree of 2.3×10 - 4 Pa, argon gas is introduced to make the internal pressure of the furnace chamber reach 0.1Mpa, an arc is generated, and the melting is repeated three times. The arc head repeatedly swings and melts 2-3cm above the weighed material. The first melting current is increased from 50A to 90A, and the melting is continued for 30s; the second melting current is increased from 45A to 90A, and the melting is continued for 30s; the third melting current is increased from 45A to 85A, and the melting is continued for 40s.

[0047] High temperature treatment sample: The ingot obtained by arc melting was placed in a sealed quartz tube and subjected to high temperature homogenization treatment at 950°C for 96 hours. Then the sample was heated to 950°C, immersed in a 0°C ice-water mixture, and cooled for 20 minutes to achieve a highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 Ti 10In4 magnetic shape memory alloy polycrystalline ingot.

[0048] But the Ni 40 Co 10 Mn 36 Ti 10 In4 No Ni 40 Co 10 Mn 36 Ti 11 In3 has small thermal hysteresis, Ni 40 Co 10 Mn 36 Ti 10 In4 No Ni 40 Co 10 Mn 36 Ti 11 The phase transition span of In3 is small, and Ni 40 Co 10 Mn 36 Ti 10 The magnetic entropy change of In4 is not as great as that of Ni 40 Co 10 Mn 36 Ti 11 In3 is high and relative to Ni 40 Co 10 Mn 36 Ti 11 In3,Ni 40 Co 10 Mn 36 Ti 10 The critical magnetic field for In4 to induce phase transition is also high.

[0049] Comparative Example 3

[0050] Weighing ratio: According to the chemical formula Ni 40 Co 10 Mn 36 The atomic percentage of In3 is 99.9% nickel, 99.9% cobalt, 99.9% manganese and 99.9% indium. The mass ratio of the components in the weighed materials is 40:10:36:3 for nickel block:cobalt block:manganese block:indium block.

[0051] Melting to prepare polycrystalline ingots: Place the weighed materials in a melting furnace and draw a vacuum to a degree of 2.3×10 - 4Pa, argon gas is introduced to make the internal pressure of the furnace chamber reach 0.1Mpa, an arc is generated, and the melting is repeated three times. The arc head repeatedly swings and melts 2-3cm above the weighed material. The first melting current is increased from 50A to 90A, and the melting is continued for 30s; the second melting current is increased from 45A to 90A, and the melting is continued for 30s; the third melting current is increased from 45A to 85A, and the melting is continued for 40s.

[0052] High temperature treatment sample: The ingot obtained by arc melting was placed in a sealed quartz tube and subjected to high temperature homogenization treatment at 950°C for 96 hours. Then the sample was heated to 950°C, immersed in a 0°C ice-water mixture, and cooled for 20 minutes to achieve a highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 In3 magnetic shape memory alloy polycrystalline ingot.

[0053] But the Ni 40 Co 10 Mn 36 In3 without Ni 40 Co 10 Mn 36 Ti 11 In3 has small thermal hysteresis, Ni 40 Co 10 Mn 36 In3 without Ni 40 Co 10 Mn 36 Ti 11 The phase transition span of In3 is small, and Ni 40 Co 10 Mn 36 The magnetic entropy change of In3 is not as great as that of Ni 40 Co 10 Mn 36 Ti 11 In3 is high and relative to Ni 40 Co 10 Mn 36 Ti 11 In3,Ni 40 Co 10 Mn 36 The critical magnetic field for In3 to induce phase transition is also high.

[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical content of the present invention.

Claims

1. A magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties, characterized in that: The chemical formula of the magnetic shape memory alloy is: Ni 40 Co 10 Mn 36 Ti 11 In3.

2. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 1, characterized in that: The weighed material is placed in a melting furnace and arc melting is used to obtain an ingot. The ingot is treated at high temperature to obtain Ni 40 Co 10 Mn 36 Ti 11 In3.

3. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 2, characterized in that: The arc melting process is as follows: vacuum is drawn to a vacuum degree of 2.3×10 -4 Pa, introduce argon gas to make the internal pressure of the furnace chamber reach 0.1Mpa, generate an arc, and repeat the melting three times. The arc head swings repeatedly 2-3cm above the weighed material for melting.

4. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 3, characterized in that: For the first smelting, the current was increased from 50A to 90A, and the smelting was continued for 30 to 50s. For the second smelting, the current was increased from 45A to 90A, and the smelting was continued for 30 to 40s. For the third smelting, the current was increased from 45A to 85A, and the smelting was continued for 30 to 40s.

5. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 2, characterized in that: The ingots were subjected to high temperature treatment steps as follows: the ingots obtained by arc melting were placed in a sealed quartz tube, subjected to high temperature homogenization treatment at 950°C for 96 hours, and then quenched to achieve highly ordered arrangement, and finally Ni 40 Co 10 Mn 36 Ti 11 In3 magnetic shape memory alloy polycrystalline ingot.

6. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 5, characterized in that: The quenching process is to heat the sample to 950°C, immerse it in a 0°C ice-water mixture, and cool it for 15-25 minutes.

7. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 2, characterized in that: The molar ratio of nickel block: cobalt block: manganese block: titanium block: indium block in the weighed material is 40:10:36-36.72:11:

3.

8. The method for preparing a magnetic shape memory alloy with low hysteresis and giant magnetocaloric properties according to claim 7, characterized in that: The purity of nickel Ni, cobalt Co, manganese Mn, titanium Ti and indium In is not less than 99.9%.

Citation Information

Patent Citations

  • Mn-rich Mn-Ni-In-Co-Cu magnetic refrigeration alloy material and preparation method thereof

    CN108677078A

  • Method for synthesizing NiCoMnIn magnetic memory alloy through combustion reaction at high temperature

    CN108950275A